Feasibility of Chatbot for Mehran UET Examination Department - Arain, Maira; Memon, Mohsin Ali; Bhatti, Sania; Arain, Maryam (Review of Information Engineering and Applications, 2019)
A chatbot system enables communication between computer and users through natural language. The university students face many problems for the queries and details regarding their examination and it is also difficult for them to physically visit the examination department frequently. The concerned authorities find it challenging to handle thousands of student queries in parallel, thus, consuming a lot of time. At present, majority of the chatbot system are available in English language. Therefore, people who are not fluent in English language cannot use these systems due to the obvious reason of language barrier. This paper focuses on the viability of a chatbot system for the examination department of Mehran University of Engineering Technology (MUET) Jamshoro. The chatbot discussed in this paper has been designed to support both Urdu and English languages. Three chatbot interfaces have been developed, Urdu typing based chatbot, English typing based chatbot and English voice based Chabot. The typing based chatbots (both English and Urdu) have been developed using AIML, and voice based chatbot is based on dialogflow called as API.ai. This study is not only concerned with the development of three interfaces of chatbot systems, but also covers their evaluation. To find best chatbot interface, a survey was conducted with engineering students of MUET Jamshoro. The results revealed that the among the three chatbot interfaces, English typing-based interface is the best due to the usability, easiness and the general understanding of queries.